Virtual Book-Based Comic Media to Improve Learning Independence of Fifth-Grade Elementary School Students - Ni Kadek Dita Julianti; I Wayan Widiana; I Made Suarjana (Universitas Pendidikan Ganesha, 2024)
Learning media is a tool that can help in the learning process in class so that the message's meaning is clearer and the educational or learning objectives can be achieved effectively and efficiently using learning media; it is easier for teachers to convey learning content. The learning media used by teachers is limited to printed books. Teachers must utilize existing technology, resulting in a need for more flexibility in the learning process and student learning independence. This research aims to produce comic products that have been tested for validity, practicality, and effectiveness in promoting student learning independence. The ADDIE development model guides this research. Research subjects include material experts, media experts, and students. The data collection method is a questionnaire method in the form of a five-point rating scale. The research results showed that the assessment from material experts was 0.96875, the assessment from learning media experts was 0.941667, and the assessment results from students were 99.04%. The effectiveness test results obtained significance (2-tailed), a result of 0.000<0.005, so h0 was rejected, and he was accepted. Based on this analysis, it can be concluded that virtual book-based comics in IPAS content are declared valid, practical, and effective for learning and increasing students' learning independence. This research implies that virtual book-based comics can be used as learning media for students in the learning process.